Analysis of Efficient Marketing Approaches: A Study on the Correlation between Celebrity Effect and Brand Marketing - Liu, Qi (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, with the continuous development of the entertainment industry, people pay more attention to entertainment and life, and can get all kinds of information about brands endorsed by celebrities from all kinds of electronic devices. The celebrity effect has gradually increased. Various brands have also invited celebrities to endorse and promote the brand, so as to increase the popularity of the brand and the increase of product profits. This paper will explore the correlation between celebrity effect and brand marketing. Through research and data analysis, the research results show that the celebrity effect will improve the brand’s market share, popularity and users’ loyalty, so as to improve the brand’s product profits, expand market share, and achieve a win-win situation for both sides. The fan economy emerged from the celebrity effect, which has had a huge impact on the stars themselves and brands, at the same time, it also proves that there is a strong correlation between celebrity effect and brand marketing.